2018
DOI: 10.1126/sciadv.1701832
|View full text |Cite
|
Sign up to set email alerts
|

Past and future drought in Mongolia

Abstract: Mongolian tree rings indicate that recent moisture extremes, although unusual, are not unprecedented in the last 2060 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 43 publications
0
65
1
Order By: Relevance
“…We found that climate‐induced increase in NEP amplitude in the 1980s and 1990s was mainly caused by elevated C sink (i.e., increased maximum NEP) and reduced C source (i.e., declined minimum NEP). It implies a faster C accumulation that likely resulted from the combination of wetter and cooler summers during those two decades, for example, the previously identified 1990s pluvial (Hessl et al, ). However, the increased NEP amplitude in the 2000s was attributed to the reduced C sink and enhanced C source (i.e., reduced maximum NEP and increased minimum NEP; Figure a), reflecting a faster C depletion due to the recent‐decade drought (Figure ).…”
Section: Resultscontrasting
confidence: 99%
“…We found that climate‐induced increase in NEP amplitude in the 1980s and 1990s was mainly caused by elevated C sink (i.e., increased maximum NEP) and reduced C source (i.e., declined minimum NEP). It implies a faster C accumulation that likely resulted from the combination of wetter and cooler summers during those two decades, for example, the previously identified 1990s pluvial (Hessl et al, ). However, the increased NEP amplitude in the 2000s was attributed to the reduced C sink and enhanced C source (i.e., reduced maximum NEP and increased minimum NEP; Figure a), reflecting a faster C depletion due to the recent‐decade drought (Figure ).…”
Section: Resultscontrasting
confidence: 99%
“…Thus, we use simulated soil moisture anomalies, integrated over all soil layers that are hydrologically active in each of the models, as a surrogate for scPDSI (SOM). However, we recognize that soil moisture and scPDSI are not fully interchangeable variables (Lehner et al 2017), and that they may behave differently under strong climatic forcing (Berg et al 2017), which is likely of minor importance for the past millennium (Hessl et al 2018).…”
Section: Datamentioning
confidence: 89%
“…However, not all studies predict such alarming scenarios. In their reconstruction and projection of past and future droughts, Hessl et al (2018) conclude that the recent extreme drought (in 2000) and pluvial (in 1990) are very rare, but not without precedent in the last 2060 years. Based on comprehensive dendrochronological studies, Slemnev et al (2012) concluded that spurts of forest regeneration in Mongolia coincide with especially moist periods that occur approximately every 40-100 years.…”
Section: Challenge 1: Adaptation To and Mitigation Of Global Warming-mentioning
confidence: 99%